Rehabilitacija oseb z okvaro hrbtenjače v času pandemije COVID-19 - Kidrič, Urška (Rehabilitacija (Ljubljana), 2021)
The COVID-19 pandemic affected the organization of work at the Department for Rehabilitation after Spinal Cord Injury of the University Rehabilitation Institute in Ljubljana. Adjustment was required in all areas of rehabilitation treatment, as well as finding new solutions and changed cooperation within the team. We adjusted to the changes on a daily basis, networking and cooperation within expert groups of different professions was essential. Together, we tried to provide an optimal rehabilitation in the given circumstances. Simultaneously with the declaration of the epidemics, home care was reduced and largely stopped, as well as the education of relatives in the ward, weekend trips to the home environment and team field work; admissions to institutionalised care were also stopped, making patient discharge more difficult. Due to the need for rehabilitation treatment after acute spinal cord injury, admissions from acute hospitals were continuing. Appropriate protective equipment was used during the rehabilitation treatment. It was necessary to ensure the prescribed distance between persons, which meant fewer patients in the therapy room and more individual program in the ward. Protective equipment also represented an obstacle in communication and contact with the patient, and wearing masks also affected the patients% endurance in therapeutic programs. Psychologically, spinal cord injury is a very stressful event, and any additional stressful situation such as COVID-19 increases the level of stress experienced and the experience of helplessness, and affects the patient's mood.
Keywords: COVID-19; epidemic; epidemija; okvara hrbtenjače; organizacija dela; organization; psihološki učinki; psychological effects; rehabilitacija; rehabilitation; Spinal Cord Injuries; terapevtski postopki; therapeutic procedures